Idiopathic granulomatous mastitis: TNFi effectivity in a retrospective inception cohort - Lermi, Nihal; Ekin, Ali; Yagiz, Burcu; Yildirim, Fatih; Albayrak, Fatih; Sunkak, Saliha; Dalkilic, Ediz (Springer London Ltd, 2025)
ObjectivesIdiopathic granulomatous mastitis is a rare, chronic, inflammatory breast disease that can mimic breast carcinoma. Histologicaly there are giant cells and epitheloid histiocytes forming non-caseating granulomas. Corticosteroids, methotrexate, azathioprine, intralesional corticosteroid injection can be used as the first step drugs in the treatment of patients with Idiopathic granulomatous mastitis, but the next step is unclear in a group of patients who are resistant to these treatments. Many of these patients also undergo unnecessary surgical interventions. Tumor necrosis factor-alpha (TNF-alpha) plays a role in maintaining the granuloma structure. There is few case reports and very limited data in the literature regarding TNF-alpha inhibitor treatment in resistant patients. Our aim is to show that TNF-alpha inhibitors may be an alternative for refractory patients in the treatment of idiopathic granulomatous mastitis.MethodsThe data of 25 female patients with idiopathic granulomatous mastitis who were refractory to conventional therapies and started TNF-alpha inhibitors were retrospectively analyzed. Pre- and post-treatment M scores of the patients were calculated.ResultsWe observed that the M-scores of our patients decreased as the duration of TNF-alpha inhibitors use increased.ConclusionOur study contains the largest number of patients with data on the use of TNF-alpha inhibitors in the treatment of idiopathic granulomatous mastitis. We believe that our study will contribute to the development of idiopathic granulomatous mastitis treatment algorithms.Key Points center dot TNF-alpha inhibitors may be an alternative for refractory patients in the treatment of idiopathic granulomatous mastitis.ConclusionOur study contains the largest number of patients with data on the use of TNF-alpha inhibitors in the treatment of idiopathic granulomatous mastitis. We believe that our study will contribute to the development of idiopathic granulomatous mastitis treatment algorithms.Key Points center dot TNF-alpha inhibitors may be an alternative for refractory patients in the treatment of idiopathic granulomatous mastitis.
Keywords: Idiopathic granulomatous mastitis; Adalimumab; Tumor necrosis factor inhibitors; Recurrence